PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN IKLIM ORGANISASI TERHADAP KOMITMEN ORGANISASI (Studi Kasus pada PT. NT Piston Ring Indonesia) - Husor Wini; Acep Rohendi; Bambang Sukajie (Jurnal AKTUAL, 2022)
In an organization or company leadership becomes very important. The leader is likened to a captain in a ship which means giving direction to his crew. The same thing happens in an organization or company. The role of the leader can influence the attitudes, ways of thinking, and actions of company employees. Employee participation and involvement appears strongly if the existing work climate in the organization stimulates employees to create high work performance. High performance will have an impact on the high commitment of employees. This is because one aspect of organizational commitment is employee involvement in the organization. Organizations need to establish a positive and conducive organizational environment and meet work standards for achieving optimal work performance. The purpose of this study was to determine how much transformational leadership style and organizational climate on organizational commitment at PT. NT Piston Rings Indonesia). The results of this study found that there was a positive and significant effect for each variable either partially or simultaneously.